Підходи до формування іншомовної комунікативної компетентності майбутніх учителів іноземних мов у США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (РВВ ЦДПУ ім. В. Винниченка, 2020)
Резюме. У статті представлені результати вивчення підходів до формування іншомовної комунікативної компетентності майбутніх учителів-філологів в університетах США. З’ясовано, що основними тенденціями, властивими сучасній системі іншомовної освіти США, є підвищення вимог до рівня сформованості іншомовної комунікативної компетентності здобувачів філолого-педагогічної освіти, а також відмова від методичного догматизму. Сучасними підходами, які набули поширеності в галузі американської іншомовної освіти є навчання іноземної мови через виконання завдань та навчання іноземної мови через зміст навчальних дисциплін/спеціальності.

Abstract. The present paper examines issues related to the evolvement of the current approaches of prospective foreign language teachers’ communicative competence development in the USA. The results of the study clearly indicate that communicative competence occupies a key stance in the structure of language teacher candidates’ professional competence, as shown by the topic’s recurrence in the standards of language teachers’ preparation and development, and also by the ongoing assessment of language proficiency of student teachers in the American universities. Based on the analysis of language teaching approaches and methods, we singled out major trends characteristic of the US foreign language education. Thus, the background paradigm reflecting the strategic aim of the sphere of language education is the communicative one i.e. language servers communication purposes. Stemming from the unique demographic composition of the American society, the educational models that evolved on this ground (bilingual, immersion) have created the necessary preconditions for reshaping language teaching approaches. The two teaching approaches that gained in popularity are the task-based language learning and content-based instruction, which rely on the concepts of the whole language approach, cooperative learning, experiential learning, and social interaction. The essence of the aforementioned approaches consists in developing language proficiency as a by-product of engaging with learning tasks and materials from different content areas. An established trend in the sphere of language education became the so-called post-method condition or the denial of existence of a universal language teaching method suitable for all language learners in any sociocultural contexts. The spread of the new approaches in language pedagogy imposes additional difficulties on language teachers, who are supposed to be able to navigate in the repertoire of teaching methods and techniques choosing the most appropriate one, and on the other hand, be well-versed in the content-areas taught by means of a foreign language.

Резюме. В статье представлены результаты изучения подходов к формированию иноязычной коммуникативной компетентности будущих учителей-филологов в университетах США. Установлено, что основными тенденциями, присущими современному иноязычному образованию США, является повышение требований к уровню иноязычной коммуникативной компетентности соискателей филолого-педагогического образования, а также отказ от методического догматизма. Современными подходами, распространенными в области иноязычного образования США является обучение иностранному языку через выполнение задач и обучения иностранному языку через содержание учебных дисциплин / специальности.
Approaches to the communicative competence development of prospective foreign language teachers in the USA
Подходы к формированию иноязычной коммуникативной компетентности будущих учителей иностранных языков в США
https://pednauk.cuspu.edu.ua/index.php/pednauk/issue/view/11/14
Keywords: іншомовна комунікативна компетентність; підготовка вчителів-філологів; іноземні мови; іншомовна освіта; підхід; метод; США